El norte - Villalpando, David (The Criterion Collection, 2008)
Mayan Indian peasants are tired of being thought of as nothing more than manual laborers. They organize an effort to improve their lot in life, but are discovered by the Guatemalan army. After the army destroys their village and family, Enrique and Rosa, a teenage brother and sister, who barely escaped the massacre, decide they must flee to United States. After receiving clandestine help from friends and humorous advice from a veteran immigrant on strategies for traveling, they make their way by truck, bus and other means to Los Angeles, where they try to make a new life as young, uneducated, and illegal immigrants.
Aspect ratio 1.78:1, 16:9 widescreen. - New, restored high-definition digital transfer, supervised and approved by director Gregory Nava
Orig.: USA, Großbritannien 1983
Enth. new audio commentary featuring Nava ; "In the Service of the Shadows: The Making of El Norte": a new video program featuring interviews with Nava, producer and co-writer Anna Thomas, actors Zaide Silvia Gutierrez and David Villalpando, and set designer David Wasco ; "The Journal of Diego Rodriguez Silva", Nava's 1972 award-winning student film ; gallery of Chiapas location-scouting photographs ; theatrical trailer ; a booklet featuring an essay by novelist Héctor Tobar and Roger Ebert's 1983 review of the film
Keywords: Illegal aliens -- California -- Los Angeles -- Drama.; Teenagers -- Drama.; Brothers and sisters -- Drama.; Feature films.; Thrillers (Motion pictures); Action and adventure films.; Jugend; Thriller; Geschwister; Actionfilm; Illegaler Einwanderer; Los Angeles, Calif.; Film; DVD-Video